(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The ideal reaction conditions for the quantitative detection of phosphate in various natural water and detergent samples were carefully researched in order to produce and preserve the colored complex product. The blue complex was identified using a simple and accurate UV-VIS spectrophotometer with a maximum wavelength of 870 nm. Even though phosphate is an essential ingredient for the development of aquatic species, it is important to know exactly how much is present because an excess amount of phosphate can eutrophic water. Since detergents are one of the sources of phosphate in natural water, determining the concentration of phosphate in detergent samples is also essential. Materials and Methods: The method is based on the addition of sodium molybdate, which causes the interaction of orthophosphate with molybdate to produce an intense, stable, and water-soluble phosphomolybdate blue complex. Then, this combination is reduced using hydrazine hydrate in a sulfuric acid solution. Results: With a correlation coefficient of 0.9944, the system complies with Lambert-Beer’s law at 870 nm in a concentration range of (0.05-9) ppm. Molar absorptivity was determined to be 12.16x103 L mol-1 cm-1 and Sandell’s sensitivity was found to be 0.0156 g cm-2. Water samples were collected from Warte, Choman, Jundeyan, and Bexal in Kurdistan’s vicinity of Soran. Further, detergent samples that were obtained from the market and their phosphate level were examined. The Bexal waterfall had the lowest concentration of phosphate, 0.18 ppm, while the Warte and Jundeyan water samples had the highest concentrations, 3.31 ppm, and 3.04 ppm, respectively. Moreover, similar phosphate concentrations in the two detergent samples were discovered to be at 20.43 and 24.76 ppm. Conclusion: The molybdenum blue reaction has been successfully employed to provide a sensitive and quick measuring method to quantify the phosphate content in various water and detergent samples using UV-VIS spectrophotometry by applying the right reaction conditions and reagent quantities.